Zuojin capsule improves T cell exhaustion and tumor immune microenvironment of hepatocellular carcinoma through the mTOR-eIF4E/p70S6K-CDK1 pathway - Hao, Liyuan; Li, Shenghao; Deng, Jiali; Hu, Xiaoyu (Frontiers in Immunology, 2025)
Background & AimsHepatocellular carcinoma (HCC) is a major health concern. T cell exhaustion (Tex), a state of T cell dysfunction characterized by reduced effector function and increased expression of inhibitory receptors. This study aimed to explore the mechanism by which Zuojin capsule (ZJC, Coptidis Rhizoma and Evodiae Fructus) treats HCC and improves Tex.MethodsTo identify HCC-related and Tex-associated targets, two HCC expression microarray datasets were integrated. Targets related to Tex were retrieved from GeneCards and Online Mendelian Inheritance in Man (OMIM) databases. Active compounds in ZJC were screened. A protein-protein interaction (PPI) network of overlapping targets was constructed using STRING to identify core functional modules. To verify the anti-proliferative effect of ZJC on HCC cells, the CCK-8 assay was performed to detect the viability of Hep3B and HepG2.2.15 cells treated with gradient concentrations of ZJC. Western Blot analysis was conducted to measure the protein expression levels of key molecules. Immunohistochemical (IHC) staining was used to assess the proliferation index of tumor cells, the infiltration of immune cells, and the expression of immune-related markers.ResultsHCC-related genes, Tex targets, and ZJC targets were identified through bioinformatics analysis, 136 overlapping targets were obtained. ZJC inhibited Hep3B/HepG2.2.15 cell proliferation with IC50 values of 310 μg/mL and 530 μg/mL, respectively. The pathway analysis conducted using DAVID revealed that the intersecting targets were mainly enriched in the mTOR signaling pathway and the transcriptional regulation process. H22 xenografts were treated with ZJC or anti-PD-1 to evaluate tumor growth and immune responses. ZJC suppressed HCC cell proliferation and reduced the expression of Ki67. Mechanistically, it downregulated phosphorylated mTOR (p-mTOR), p-eIF4E, and p-p70S6K, and this downregulated state could be reversed by the restoration of mTOR activators. ZJC reduced the expression of cyclin-dependent kinase 1 (CDK1). In HCC tissues, M1 macrophages were reduced, while M2 macrophages and exhausted T cells were accumulated. ZJC treatment inhibited tumor growth and modulated immune infiltration. Additionally, ZJC and anti-PD-1 promoted the expression or aggregation of CD8-positive cells. In addition, the control group showed relatively high positive staining for CD163, whereas ZJC and anti-PD-1 inhibited the expression or aggregation of CD163-positive cells.ConclusionZJC exerts dual anti-tumor effects by inhibiting the mTOR-eIF4E/p70S6K-CDK1 pathway and remodeling the immunosuppressive microenvironment of HCC.